THE IMPACT OF APPLYING TOTAL QUALITY MANAGEMENT PRINCIPLES ON THE OVERALL HOSPITAL EFFECTIVENESS: AN EMPIRICAL STUDY ON THE HCAC ACCREDITED GOVERNMENTAL HOSPITALS IN JORDAN - Abd El-Moneim A. El-Tohamy; Atef T Al Raoush (European Scientific Journal, ESJ, 2015)
The present study was conducted to bring the attention to the importance of applying total quality management (TQM) and their effects on organizational effectiveness, and particularly the hospital effectiveness. The main objective of the present study was to investigate the impact of applying TQM on the overall hospital effectiveness in the accredited governmental hospitals in Jordan that accredited from Health Care Accreditation Council (HCAC). The study population represented all health care professionals working in the five HCAC accredited governmental hospitals who were working for more than three years in the same hospitals. Study sample included 1290 employees. The response rate was 83.6 % of the total questionnaires distributed. TQM principles were: Leadership commitment to quality, Customer focus, Continuous improvement, Teamwork, Employee involvement, education and training. Study findings showed a significant impact of all TQM principles on the overall hospital effectiveness (p< 0.05). Using multiple linear regression analysis showed that TQM is a strong predictor of hospital performance (Beta =0.818, t=46.613, R2= 0.669, and p value = 0.000). Taken together, applying the principles of TQM increases the overall hospital effectiveness in the HCAC accredited governmental hospitals in Jordan.